Deconstructing Hegemonic Masculinity: The Blood Pact as a Semiotic Sign of Dumbledore’s Vulnerability in “Fantastic Beasts”: Dekonstruksi Maskulinitas Hegemonik: Perjanjian Darah sebagai Tanda Semiotik Kerentanan Dumbledore dalam “Fantastic Beast“ - Pramono, Anggreini Putri; Syaputri, Wuri (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Albus Dumbledore is consistently portrayed as a rational and wise hero. However, this image is turned on its head in the film “Fantastic Beasts: The Secrets of Dumbledore”, in which he appears as a vulnerable figure unable to act on his own. This study aims to uncover the latent meaning of the Blood Pact in shaping Dumbledore’s vulnerability and to demonstrate the deconstruction of his masculinity. Using a descriptive qualitative method, this study integrates Peirce’s triadic semiotics (representamen-object-interpretant) and Derrida’s deconstruction (phalogocentrism, trace, différance, and aporia) to examine indexical signs and the collapse of heroic authority. The findings indicate that the Blood Pact is not merely an accessory but an artifact that bears traces of the past and serves as both a physical and logical obstacle for Dumbledore. He thus becomes a reluctant hero, shackled both physically and logically. Ultimately, his acceptance of the past and the courage to acknowledge his weaknesses actually reconstruct his authentic heroism amid emotional dilemmas.